The political, social and economic context of changing water policy in South Africa: post-1994 - van Koppen, Barbara; Schreiner, B.; Fakir, S. (Springer, 2010)
This chapter describes the political, social and economic context in which South Africa's water reform was designed and implemented. The water reform was part of the nation's wider transformation after 1994 from white minority rule and territorial and institutional segregation, to a democratic, non-racial state. This implied a major challenge to redress the legacy of gross inequities in access to water for domestic and productive uses and the persistently high poverty levels, especially in the rural areas. For a better understanding of the continuities and changes from the past for all aspects of water reform discussed in this volume, the history of water development and management in apartheid South Africa is traced. This encompasses the removal of land and water rights from black South Africans by the early 1900s; the hydraulic mission for white agriculture throughout the twentieth century; and the emergence of the centrally planned, urban-industrialized water economy from the 1970s onwards. Many concepts that would globally be seen as 'best practice' Integrated Water Resource Management according to the Dublin principles of 1992 originate in that era. The chapter concludes by introducing the subsequent chapters in this light.